Effects of cultivars and starch preparation methods on Japanese potato starch properties - Noda, Takahiro; Suzuki, Tatsuro; Hashimoto, Naoto; Nagasawa, Koichi; Yamauchi, Hiroaki; Sarker, Md. Zaidul Islam (2012)
Potato starch is one of the important agricultural products in Hokkaido, the northernmost and second largest island of Japan. The objective of this investigation was to evaluate the effects of cultivars and starch preparation methods on the quality parameters of Japanese potato starch. Potato starches from four cultivars: Hokkaikogane, Eniwa,Benimaru, and Norin No. 1, grown over a period of several years in Hokkaido were used. The starches produced with tap water in a local starch factory and with distilled water in a laboratory were investigated for phosphorus content, median granule size, and peak viscosity and breakdown as determined with a Rapid Visco Analyzer. The starch’s median granule size among potato cultivars varied in the following order: Benimaru (43.1 µm) > Hokkaikogane (39.1 µm) ≈ Eniwa (38.2 µm) > Norin No. 1 (33.9 µm). We found that starches of Hokkaikogane and Eniwa, both with a measurably higher phosphorus content, displayed significantly higher peak viscosity and breakdown than those of Benimaru and Norin No. 1. Even within the same cultivar, the starch preparation method has a significant impact on peak viscosity and breakdown. The starches produced with tap water in the factory showed decreased values of peak viscosity and breakdown compared to those produced with distilled water in a laboratory. However, the starch preparation method had a little or no influence on phosphorus content. Median granule size was also completely independent of the preparation method.